High-stability doped sodium ferric sulfate positive electrode material and preparation method thereof
Through the co-doping technology of Ca, Zn and PO43- and carbon nanotube composite, the problems of poor conductivity and water sensitivity of sodium ferrosulfate material are solved, and a high-magnification cycle stability and air stability are achieved.
Patent Information
- Application Number
- CN202411893355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The intrinsic conductivity of sodium ferrous sulfate material is poor, resulting in low rate performance and is sensitive to moisture, affecting its air stability.
The co-doping technology of Ca, Zn and PO43- is used to modify the sodium iron sulfate crystal lattice and composite it with carbon nanotubes. The composite material of iron zinc calcium sulfate and carbon nanotubes was prepared by solid phase physical ball milling and low-temperature calcination.
The conductivity and water resistance of sodium ferrous sulfate material are significantly improved, excellent rate performance and air stability are obtained, and the circulation stability is more than 6,000 times.
Smart Images

Figure CN119764381A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery electrode materials, and specifically relates to a highly stable doped sodium iron sulfate positive electrode material and a preparation method thereof. Background Art
[0002] As an electrochemical energy storage device with low raw material cost and high safety, sodium ion battery has broad application prospects in the field of large-scale energy storage. As a key component of sodium ion battery, the positive electrode has a decisive influence on the performance and cost of the entire battery. At present, there are three mainstream choices for sodium ion battery positive electrode materials, transition metal layered oxides, Prussian blue analogs, and polyanion compounds. Among them, transition metal layered oxides are relatively expensive, and irreversible phase changes occur during long-cycle cycles, affecting their cycle stability; although Prussian blue analogs are relatively low in cost, the difficult-to-control crystalline water in their molecular structure limits the large-scale preparation of materials. In comparison, polyanionic sodium iron sulfate positive electrode materials have attracted widespread attention due to their low raw material cost, high operating voltage (about 3.8V) and stable cycle performance. However, due to the poor intrinsic conductivity of sodium iron sulfate materials, their rate charge and discharge performance is limited. In addition, sodium iron sulfate materials are sensitive to moisture. Even trace amounts of moisture in the air can be easily absorbed by sodium iron sulfate crystals, thereby destroying their crystalline structure. Therefore, how to improve the rate performance of sodium iron sulfate materials while maintaining their stability in the air is the key to large-scale application of sodium iron sulfate materials.
[0003] In view of the poor conductivity of sodium ferric sulfate, existing studies have mostly used composite conductive carbon materials for modification, such as (CN 117720132 A, CN 118969995 A, Science Bulletin, 2023, 68: 1894–1903, Nature Communications, 2023, 14: 3701). Using these existing technologies, although it is also possible to synthesize sodium ferric sulfate composite materials with significantly improved conductivity and obtain good cycle stability. However, the sodium storage capacity, cycle performance and water resistance of the material at high rates are still not ideal. The main reason is that the composite between sodium ferric sulfate and carbon materials belongs to physical contact composite, which does not change the problem of poor intrinsic conductivity and sensitivity to water of sodium ferric sulfate crystals. Summary of the invention
[0004] Aiming at the problem that the sodium storage capacity, cycle performance and water resistance of sodium iron sulfate at high rate are poor, the present invention provides a novel sodium iron sulfate zinc calcium phosphate composite electrode material and a preparation method thereof, and adopts a simple solid phase physical ball milling and low temperature calcination method to prepare a sodium iron sulfate zinc calcium phosphate and carbon nanotube composite material. 3- The co-doping greatly improved the intrinsic conductivity of sodium iron sulfate crystals while reducing the material's sensitivity to moisture, thereby obtaining a sodium-ion battery composite positive electrode material with excellent rate performance and air stability.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A highly stable doped sodium iron sulfate positive electrode material comprises sodium zinc calcium iron phosphate sulfate particles and carbon nanotubes.
[0007] Furthermore, the mass ratio of the sodium calcium zinc sulfate iron phosphate particles to the carbon nanotubes is 85-95:5-15.
[0008] Further, the chemical formula of the sodium calcium zinc ferric sulfate phosphate is: Na 2+2x Ca y Zn z Fe 2-x-y-z (SO4) 3-y-z (PO4) 2(y+z) / 3 , where x ranges from 0.20 to 0.35, y ranges from 0.03 to 0.12, and z ranges from 0.03 to 0.12.
[0009] A method for preparing a highly stable doped sodium iron sulfate positive electrode material comprises the following steps:
[0010] Step 1, ball-milling anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous calcium phosphate, anhydrous zinc phosphate and carbon nanotubes in an inert atmosphere ball mill to obtain a calcined precursor;
[0011] Step 2, placing the calcined precursor in an inert atmosphere tube furnace for calcining at 360-400° C., with a heating rate of 1.5-2° C. / min and a calcining time of 16-24 h to obtain a sodium sulfate iron zinc calcium phosphate composite electrode material.
[0012] Furthermore, the anhydrous ferrous sulfate is prepared by heat treating ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 8 to 12 hours.
[0013] Furthermore, the mass ratio of the anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous calcium phosphate, anhydrous zinc phosphate and carbon nanotubes is: 46.93-50.88: 32.78-41.98: 0.60-2.72: 0.74-3.38: 5.00-15.00.
[0014] Furthermore, in the step 1, the gas filled in the inert atmosphere ball milling jar is argon or nitrogen, and the ball milling time is 10 to 15 hours.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] (1) The present invention aims to solve the problems of poor intrinsic conductivity, low rate performance and poor air stability of the current sodium iron sulfate electrode material. The present invention introduces Ca, Zn and PO43- to modify the sodium iron sulfate lattice. The co-doping of Ca and Zn can change the sodium iron sulfate unit cell to produce distortion, expand the lattice parameter, improve its ion conductivity, and facilitate the transmission of sodium ions. At the same time, the interaction between the two doping ions and the electron cloud of Fe atoms can effectively reduce the band gap width of sodium iron sulfate, so that its electronic conductivity is also improved. In addition, the synchronously realized PO4 3- The successful doping can effectively improve the material's binding energy to water and improve its water resistance. Combined with the good conductive network of carbon nanotubes, the conductivity and air stability of the composite material can be significantly improved.
[0017] (2) The electrode material provided by the present invention has the advantages of simple and convenient preparation method, low cost, good air stability and rate performance, good cycle stability (>6000 times), etc., and has strong market competitiveness in the field of large-scale energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The charge and discharge curve diagram corresponding to the sodium ion battery prepared from the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 1 of the present invention;
[0019] Figure 2 The rate performance diagram corresponding to the sodium ion battery prepared from the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 2 of the present invention;
[0020] Figure 3 The long cycle diagram corresponding to the sodium ion battery prepared from the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 2 of the present invention;
[0021] Figure 4 The XRD pattern of the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 3 of the present invention;
[0022] Figure 5This is a scanning electron microscope image corresponding to the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 3 of the present invention;
[0023] Figure 6 This is the XRD pattern of the sodium iron zinc calcium sulfate phosphate composite positive electrode material obtained in Example 3 of the present invention after being placed in air for 7 days. DETAILED DESCRIPTION
[0024] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.
[0025] Example 1
[0026] S1, heat-treat 48.37 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 8 h to obtain 26.65 g of anhydrous ferrous sulfate.
[0027] S2, 26.65 g of anhydrous ferrous sulfate, 17.04 g of anhydrous sodium sulfate, 0.31 g of anhydrous calcium phosphate, 0.386 g of anhydrous zinc phosphate and 2.42 g of carbon nanotubes were ball-milled in an inert atmosphere ball mill for 10 h to obtain a calcined precursor.
[0028] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 360°C, with a heating rate of 1.8°C / min and a calcination time of 16h to obtain a sodium iron sulfate zinc calcium phosphate composite electrode material, wherein the sodium iron sulfate zinc calcium phosphate molecular formula is Na 2.4 Ca 0.03 Zn 0.03 Fe 1.74 (SO4) 2.94 (PO4) 0.04 , the carbon nanotube content is 5.17%wt.
[0029] The obtained sodium ion battery is prepared by using the sodium iron phosphate calcium zinc sulfate composite positive electrode material, and the corresponding charge and discharge curve is shown in the figure below. Figure 1 As shown, it is proved that the discharge specific capacity of the material can still reach more than 85 mAh / g at a current density of 1C (120 mAh / g).
[0030] Example 2
[0031] S1, heat-treat 43.37 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 10 h to obtain 23.71 g of anhydrous ferrous sulfate.
[0032] S2, 23.71 g of anhydrous ferrous sulfate, 17.04 g of anhydrous sodium sulfate, 1.24 g of anhydrous calcium phosphate, 1.54 g of anhydrous zinc phosphate and 3.93 g of carbon nanotubes were ball-milled in an inert atmosphere ball mill for 10 h to obtain a calcined precursor.
[0033] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 380°C, with a heating rate of 1.9°C / min and a calcination time of 18h to obtain a sodium iron sulfate zinc calcium phosphate composite electrode material, wherein the sodium iron sulfate zinc calcium phosphate molecular formula is Na 2.4 Ca 0.12 Zn 0.12 Fe 1.56 (SO4) 2.76 (PO4) 0.18 , the carbon nanotube content is 8.28%wt.
[0034] The rate performance diagram corresponding to the sodium ion battery prepared by the sulfate iron phosphate calcium zinc sodium composite positive electrode material is obtained, such as Figure 2 As shown, the results show that the material still has a cycle capacity of 60mAh / g at a large rate of 100C; the long cycle diagram corresponding to the sodium ion battery is shown in Figure 3 As shown, the results show that the capacity retention rate of the material reaches more than 90% after 6000 cycles at a high current of 50C, and it has excellent high-rate cycle stability.
[0035] Example 3
[0036] S1, heat-treat 41.7 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 12 h to obtain 22.8 g of anhydrous ferrous sulfate.
[0037] S2, 22.8 g of anhydrous ferrous sulfate, 19.17 g of anhydrous sodium sulfate, 1.24 g of anhydrous calcium phosphate, 0.386 g of anhydrous zinc phosphate and 5.42 g of carbon nanotubes were ball-milled in an inert atmosphere ball mill for 14 h to obtain a calcined precursor.
[0038] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 390°C, with a heating rate of 1.5°C / min and a calcination time of 24h to obtain a sodium iron sulfate zinc calcium phosphate composite electrode material, wherein the sodium iron sulfate zinc calcium phosphate molecular formula is Na 2.7 Ca 0.12 Zn 0.03 Fe 1.50 (SO4) 2.85 (PO4) 0.1 , the carbon nanotube content is 11.1%wt.
[0039] The XRD pattern of the sodium iron zinc calcium sulfate phosphate composite positive electrode material is obtained, such as Figure 4As shown in the figure, the XRD diffraction peak is sharp and there is no impurity phase, which proves that the crystal phase is of high purity and complete crystal form; the corresponding scanning electron microscope image of the sodium iron zinc calcium sulfate phosphate composite positive electrode material is as follows Figure 5 As shown, it can be clearly seen that the crystal size of sodium iron zinc calcium sulfate phosphate is uniform, and the particle size is between 1 and 10 microns; the XRD pattern of the sodium iron zinc calcium sulfate phosphate composite positive electrode material measured after being placed in the air for 7 days, as shown Figure 6 As shown, the XRD diffraction peak shape has not changed substantially, and no new impurity phase has appeared, proving its excellent air stability.
[0040] Example 4
[0041] S1, heat-treat 42.53 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 8 h to obtain 23.25 g of anhydrous ferrous sulfate.
[0042] S2, 23.25 g of anhydrous ferrous sulfate, 19.17 g of anhydrous sodium sulfate, 0.62 g of anhydrous calcium phosphate, 0.772 g of anhydrous zinc phosphate and 6.58 g of carbon nanotubes were ball-milled in an inert atmosphere ball mill for 15 h to obtain a calcined precursor.
[0043] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 360°C, with a heating rate of 1.5°C / min and a calcination time of 20h to obtain a sodium iron sulfate zinc calcium phosphate composite electrode material, wherein the sodium iron sulfate zinc calcium phosphate molecular formula is Na 2.7 Ca 0.06 Zn 0.06 Fe 1.53 (SO4) 2.88 (PO4) 0.08 , the carbon nanotube content is 13.1%wt.
[0044] Example 5
[0045] S1, heat-treat 43.92 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 10 h to obtain 24.02 g of anhydrous ferrous sulfate.
[0046] S2, 24.02 g of anhydrous ferrous sulfate, 18.46 g of anhydrous sodium sulfate, 0.62 g of anhydrous calcium phosphate, 0.772 g of anhydrous zinc phosphate and 6.42 g of carbon nanotubes were ball-milled in an inert atmosphere ball mill for 12 h to obtain a calcined precursor.
[0047] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 370°C, with a heating rate of 1.5°C / min and a calcination time of 18h to obtain a sodium iron sulfate zinc calcium phosphate composite electrode material, wherein the sodium iron sulfate zinc calcium phosphate molecular formula is Na 2.6 Ca 0.06 Zn0.06 Fe 1.58 (SO4) 2.88 (PO4) 0.08 , the carbon nanotube content is 12.77%wt.
[0048] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. A highly stable doped sodium iron sulfate positive electrode material, characterized in that: Includes calcium zinc sulfate sodium iron phosphate particles and carbon nanotubes.
2. The highly stable doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The mass ratio of the sodium calcium zinc ferric sulfate phosphate particles to the carbon nanotubes is 85-95:5-15.
3. The highly stable doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The chemical formula of the sodium zinc calcium sulfate ferric phosphate is: Na 2+2x Ca y Zn z Fe 2-x-y-z (SO4) 3-y-z (PO4) 2(y+z) / 3 , where x ranges from 0.20 to 0.35, y ranges from 0.03 to 0.12, and z ranges from 0.03 to 0.
12.
4. The method for preparing a highly stable doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1, ball-milling anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous calcium phosphate, anhydrous zinc phosphate and carbon nanotubes in an inert atmosphere ball mill to obtain a calcined precursor; Step 2: placing the calcined precursor in an inert atmosphere tube furnace for calcination to obtain a sodium sulfate iron zinc calcium phosphate composite electrode material.
5. The method for preparing a highly stable doped sodium iron sulfate positive electrode material according to claim 4, characterized in that: The anhydrous ferrous sulfate is prepared by subjecting ferrous sulfate heptahydrate to heat treatment at 250° C. in an inert atmosphere tube furnace for 8 to 12 hours.
6. The method for preparing a highly stable doped sodium iron sulfate positive electrode material according to claim 4, characterized in that: The mass ratio of the anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous calcium phosphate, anhydrous zinc phosphate and carbon nanotubes is: 46.93-50.88: 32.78-41.98: 0.60-2.72: 0.74-3.38: 5.00-15.
00.
7. The method for preparing a highly stable doped sodium iron sulfate positive electrode material according to claim 4, characterized in that: In the step 1, the gas filled in the inert atmosphere ball milling jar is argon or nitrogen, and the ball milling time is 10 to 15 hours.
8. The method for preparing a highly stable doped sodium iron sulfate positive electrode material according to claim 4, characterized in that: In step 2, the calcination temperature is 360-400° C., the heating rate is 1.5-2° C. / min, and the calcination time is 16-24 h.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN115050957A
Positive electrode material, positive electrode plate and sodium ion battery
CN116364915A
Element-doped dual-carbon modified sodium ferrous sulfate positive electrode material and preparation method and application thereof
CN118099392A
Preparation method of simple carbon-coated anion-doped sodium ferric sulfate as sodium ion battery positive electrode material
CN118164458A
Nickel-rich high-voltage sodium-ion positive electrode material for battery, preparation method therefor, and application thereof
WO2023093180A1
Cited By
Method for preparing moisture-resistant sodium ferric sulfate from pyrite
CN121107464A
A method for preparing moisture-resistant sodium ferrous sulfate by using pyrite
CN121107464B